The Chinese Nationalism and Foreign Policy Component in Mass Consciousness in China - Kuznetsov, Dmitry V. (Overcoming Controversies in East Asia, 2017)
The research describes the phenomenon of Chinese nationalism in the context of the foreign policy component of the mass consciousness of residents in China. The ideas of Chinese nationalism become more popular both on the individual level and the level of mass consciousness. This is according to opinion polls, data from the media, as well as views widely spread among the intellectual elite. Between 2000–2010 there was a significant rise of nationalism in China. The reason was the transformation of Chinese public opinion. Under the influence of progress in the development of China, people have come to realize that modern China certainly plays a crucial role in world politics and economics. A characteristic feature of modern Chinese nationalism is that it proliferates far outside of China. Currently, its main content is a growing anti-American and anti-Japanese views. The ideas of modern Chinese nationalism have become most prevalent among the younger generation of Chinese citizens. These processes are partially controlled by the PRC authorities, who need the population to have certain ideological orientation. Considering the rise of nationalism in China we can see the appearance of the ‘Chinese Dream’ concept in 2012.